Writing-to-learn in a higher education writing intensive tutorial programme: student collaboration and confidence building - Maistry, Suriamurthee Moonsamy; Bargate, Karen (South African Journal of Higher Education, 2016)
This paper emanates from a study, which focused on Managerial Accounting and Financial Management students’ experiences of learning in a Writing Intensive Tutorial (WIT) Programme. Higher education students often do not appreciate or realise the benefits of working collaboratively with other students. The WIT Programme was based on the principles of collaborative participation among the students and writing-to-learn. Interactive Qualitative Analysis (IQA) (Northcutt and McCoy 2004) informed the research design and data analysis. Following IQA protocols, nine affinities (themes) were generated to describe students’ experiences of learning in the WIT programme. This paper reports on the affinities of personal confidence and interaction. Findings suggest that collaborative engagement in writing to learn activities, designed according to tight specifications facilitates a process of focused and directed interaction among students. This has important implications for higher education programme design especially in professional programmes where the requirements of the profession include interaction and personal confidence.